ACTINOMYCOSIS IN A CROSSBRED COW - A CASE REPORT - Kumar, Ankit; Kumar, Parmod; Charya, Gaurav; Kumar, Tarun; Sindhu, Nilesh; Sharma, Satbir (Indian Journal of Veterinary Sciences and Biotechnology, 2015)
Actinomycosis also called as lumpy jaw is a local or systemic, chronic, suppurative and granulomatous disease characterized by granulomatous abscess; frequently involves mandible, maxillae or other bony tissue in the head, though the rare cases may involve soft tissues, particularly the alimentary tract (Bertone and Rebhum, 1984). It is caused by Actinomyces bovis, a gram positive, rod shaped non-motile, non-sporulating, anaerobic bacterium which is normal inhabitant of oral and pharyngeal mucous membranes (Radostits et al., 2005). The disease is seen when A. bovis is introduced to underlying soft tissue via penetrating wounds of the oral mucosa from wire or coarse hay or sticks. Various treatment protocols have been documented in the literature for the lumpy jaw but with sub satisfactory responses (Brunton et al. 2005; Mettler et al., 2009). The present report of lumpy jaw revealed complete recovery with combination of both surgical intervention and drug therapy.